Camomile-ELSE: creating plugins with Pure Data patches and the ELSE library - Astorga, E. M. V.; Porres, Alexandre Torres (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2021)
Camomile is an open source project that turns patches made in the Pure Data programming language into plugins (VST, VST3, LV2 and Audio Unit) so you can load them in any plugin host on Windows, Linux and MacOS. We have a fork of this project that embeds the ELSE library of Pure Data externals into camomile so you dont have to only rely on the limited set of native Pure Data objects. This paper describes the potential of the Camomile project, how it makes the creation of plugins very accessible to people without a background in computer science and also how this process is improved by including the extensive ELSE library. We also offer an overview of similar projects and the technical details of including the ELSE library into the camomile project.